The Authority and Legal Validity of Notarial Deeds Drawn Up by A Notary Who is a Suspect - Ni Wayan Yunika Duarta; I Wayan Wesna Astara; I Ketut Kasta Arya Wijaya (Transpublika Publisher, 2026)
The growing number of notaries in Indonesia being designated as criminal suspects has raised pressing questions regarding the continuity of their authority and the legal standing of the deeds they have executed, underscoring the need for a clear normative framework on this issue. This study aims to analyze the legal implications of the designation of a Notary as a suspect on their authority and the validity of authentic deeds under Indonesian positive law, encompassing both the authority retained by a notary in carrying out his duties while holding suspect status and the legal consequences befalling authentic deeds executed during this period. This research employs a normative legal method with statutory and conceptual approaches. The results show that the designation of a Notary as a suspect does not automatically limit or revoke their authority, as the Law on Notary Position does not recognize suspect status as a ground for dismissal. Article 9 paragraph (1) of the Notary Law provides a limitative regulation on temporary suspension, including when a Notary is under detention. Furthermore, authentic deeds executed by a Notary holding suspect status remain valid and retain their full evidentiary power, provided they comply with the requirements set forth in Articles 1868 and 1870 of the Civil Code. A suspect's status does not impact deed validity unless proven legal violation in execution occurs causing degradation or nullification of the deed. Thus, while it lacks direct legal consequences suspect status carries sociological implications harming public trust and legal certainty.